2021
DOI: 10.1155/2021/5580039
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Nutritional Malpractices, Motivational Drivers, and Consequences in Pregnant Women: Evidence from Recent Literature and Program Implications in Ethiopia

Abstract: Maternal nutrition is very important for the wellbeing of pregnant women, childbirth, and lactating women, which are crucial and meant for the wellbeing of a mother and newborn baby. This narrative review discusses nutritional malpractices, motivational drivers, and their consequences typically from Ethiopian pregnant women’s context. Different studies (regarding less of study design and type) done among pregnant women (aged 15–49 years) by considering pregnancy-related outcomes and timing of nutritional malpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 82 publications
2
4
0
Order By: Relevance
“…Pregnant women who had practiced pica have a higher likelihood of experiencing food cravings as compared to their counterparts. Consistent with our study result different studies revealed that craving for nonfood items reduces the intake of nutritious foods which in turn leads to inadequate dietary intake of essential nutrients [ 8 , 20 , 21 ].On the other hand, our study result found that pregnant women who skipped meals were more likely to experience food cravings than women who did not skip meals. Skipping meals during pregnancy can affect the blood glucose level and also increase cravings for junk foods, which have empty calories to meet the nutritional demand of the pregnant mother [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Pregnant women who had practiced pica have a higher likelihood of experiencing food cravings as compared to their counterparts. Consistent with our study result different studies revealed that craving for nonfood items reduces the intake of nutritious foods which in turn leads to inadequate dietary intake of essential nutrients [ 8 , 20 , 21 ].On the other hand, our study result found that pregnant women who skipped meals were more likely to experience food cravings than women who did not skip meals. Skipping meals during pregnancy can affect the blood glucose level and also increase cravings for junk foods, which have empty calories to meet the nutritional demand of the pregnant mother [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…For instance, in a community-based study in Boricha Woreda, Southern Ethiopia, nearly, seven in ten (69.2%) pregnant women were averted to at least one food (Moges et al, 2015). Another possible reason for the difference in study findings is that during pregnancy, motivation for eating a healthy diet may change compared to the non-pregnant state, as women prepare for motherhood and consider the impact of their dietary intake on the child's health (Forbes et al, 2018;Kibr, 2021). The current finding has important implications on the general wellbeing of both the mother and the baby, considering that excess fat intake could contribute to unhealthy weight gain in the pregnant women (WHO, 2020), and yet essential fatty acids such as DHA and EPA are essential for foetal growth and development (Coletta et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Throughout pregnancy, women need proper nutrition for a healthy outcome; they also need more food, a varied diet, increased calorie intake, and micronutrient supplements [9]. Poor maternal nutrition habits such as an inadequate diet, low meal frequency, consuming excess tea and coffee during meals, and food aversion are associated with anemia and can result in a low intake of vital nutrients like protein, vitamin C, vitamin A, iron, and vitamins [2,10].…”
Section: Introductionmentioning
confidence: 99%